Non‐Kinetic Effects Convolute Activity and Tafel Analysis for the Alkaline Oxygen Evolution Reaction on NiFeOOH Electrocatalysts. (10th January 2023) - van der Heijden, Onno; Park, Sunghak; Eggebeen, Jordy J. J.; Koper, Marc T. M.
Abstract: A large variety of nickel‐based catalysts has been investigated for the oxygen evolution reaction (OER) in alkaline media. However, their reported activity, as well as Tafel slope values, vary greatly. To understand this variation, we studied electrodeposited Ni80 Fe20 OOH catalysts with different loadings at varying rotation rates, hydroxide concentrations, with or without sonication. We show that, at low current density (<5 mA cm −2 ), the Tafel slope value is ≈30 mV dec −1 for Ni80 Fe20 OOH. At higher polarization, the Tafel slope continuously increases and is dependent on rotation rate, loading, hydroxide concentration and sonication. These Tafel slope values are convoluted by non‐kinetic effects, such as bubbles, potential‐dependent changes in ohmic resistance and (internal) OH − gradients. As best practise, we suggest that Tafel slopes should be plotted vs. current or potential. In such a plot, it can be appreciated if there is a kinetic Tafel slope or if the observed Tafel slope is influenced by non‐kinetic effects. Abstract : We studied NiFeOOH catalysts for the alkaline oxygen evolution reaction (OER) with different loading, varying rotation rate, hydroxide concentration and with and without sonication. We show that the Tafel slope initially is ≈30 mV dec −1 for NiFeOOH in 0.05–0.2 M KOH, and at higher polarization the Tafel slope continually increases due to bubbles, potential‐dependent changes in ohmic resistance, and (internal) OH − gradients.